Effect of Continuous-Flow Left Ventricular Assist Device Support on Coronary Artery Endothelial Function in Ischemic and Nonischemic Cardiomyopathy. (August 2019) - Symons, J. David; Deeter, Lance; Deeter, Nicholas; Bonn, Trevor; Cho, Jae Min; Ferrin, Peter; McCreath, Lauren; Diakos, Nikolaos A.; Taleb, Iosif; Alharethi, Rami; McKellar, Stephen; Wever-Pinzon, Omar; et al.
Abstract : Background: The coronary vasculature encounters a reduction in pulsatility after implementing durable continuous-flow left ventricular assist device (CF-LVAD) circulatory support. Evidence exists that appropriate pulsatility is required to maintain endothelial cell homeostasis. We hypothesized that coronary artery endothelial function would be impaired after CF-LVAD intervention. Methods and Results: Coronary arteries from patients with end-stage heart failure caused by ischemic cardiomyopathy (ICM; n=16) or non-ICM (n=22) cardiomyopathy were isolated from the left ventricular apical core, which was removed for the CF-LVAD implantation. In 11 of these patients, paired coronary arteries were obtained from an adjacent region of myocardium after the CF-LVAD intervention (n=6 ICM, 5 non-ICM). Vascular function was assessed ex vivo using isometric tension procedures in these patients and in 7 nonfailing donor controls. Maximal endothelium-dependent vasorelaxation to BK (bradykinin; 10 − 6 –10 − 10 M) was blunted ( P <0.05) in arteries from patients with ICM compared with non-ICM and donor controls, whereas responses to sodium nitroprusside (10 −4 –10 −9 M) were similar among the groups. Contrary to our hypothesis, vasorelaxation responses to BK and sodium nitroprusside were similar before and 219±37 days after CF-LVAD support. Of these patients, an exploratory subgroup analysis revealed that BK-induced coronary artery vasorelaxation was greater ( P <0.05) after (87±6%) versus before (54±14%) CF-LVAD intervention in ICM patients, whereas sodium nitroprusside–evoked responses were similar. Conclusions: Coronary artery endothelial function is not impaired by durable CF-LVAD support and in ICM patients appears to be improved. Investigating coronary endothelial function using in vivo approaches in a larger patient population is warranted. Abstract : Supplemental Digital Content is available in the text.